Anatomical Structure and Copper Microdistribution in Mechanical, Biological, and Laser Incised Spruce and Larch Refractory Woods - Davut Bakir (BioResources, 2023)
The anatomical structure of wood and the application of three different incision pretreatments affect the distribution of preservatives in refractory woods. This study focused on Picea orientalis (L.) Peterm.) and Larix decidua Mill. and investigated the distribution of copper-based preservatives in the wood microstructure. Different incision pretreatments were applied before impregnation to increase the permeability of spruce and larch sapwood samples. After the incision pretreatments, transverse cross-sectional surfaces of the samples were sealed with polyurethane-based paint to prevent excessive preservative uptake into open ends of longitudinal tracheid lumens. The samples were then impregnated with Celcure C4, by applying a vacuum method. The structure of wood samples with preservatives before and after the incision pretreatments were observed. Copper microdistribution was observed to increase significantly in refractory wood species after different incision pretreatments, especially in larch wood. The degradation of pits caused by biological incision effectively increased the microdistribution of copper. The difference in the microdistribution of increased copper with the laser and mechanical incision pretreatments – following the same incision model – was attributed to the different anatomical structure and density of spruce and larch wood species and the fact that the hole depth and geometry were different in the laser and mechanical incision processes.